2018
DOI: 10.24925/turjaf.v6i10.1469-1473.2083
|View full text |Cite
|
Sign up to set email alerts
|

In Ovo β-Alanin Solüsyonu Alan Yeni Çıkmış Etlik Piliç Civcivlerinde Kuluçka Randımanı, Bazı Kuluçka Parametreleri, Kalite Skoru ve Yaşama Gücü

Abstract: This study was conducted to evaluate the effects of In ovo injection of β-Alanine which is a modified form of the alanine amino acid on hatchability, hatching weight, chick quality score and survival in broiler breeder eggs. For this purpose, 120 fertile eggs from Ross 308 breeder (32-week-old) were allocated randomly to four groups with 3 replicates. Except the negative control group eggs (non injected; NC), to the amniotic fluid of the eggs in the other 3 groups were injected with 1 ml solutions 0.9% salt (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Therefore, hatching weight alone should not be considered a good indicator of chick quality (Decuypere & Bruggeman, 2007). In the light of the present results (Table 2) and with supporting evidence from other studies (Kop-Bozbay et al, 2018;Araújo et al, 2019), it may be concluded that a higher number of chicks of better quality could be obtained with in ovo βA injection on the 17th day of incubation. Therefore, chicks fed βA in ovo are healthier and have higher life force than their unsupplemented counterparts (Tona et al, 2003;Decuypere & Bruggeman, 2007).…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…Therefore, hatching weight alone should not be considered a good indicator of chick quality (Decuypere & Bruggeman, 2007). In the light of the present results (Table 2) and with supporting evidence from other studies (Kop-Bozbay et al, 2018;Araújo et al, 2019), it may be concluded that a higher number of chicks of better quality could be obtained with in ovo βA injection on the 17th day of incubation. Therefore, chicks fed βA in ovo are healthier and have higher life force than their unsupplemented counterparts (Tona et al, 2003;Decuypere & Bruggeman, 2007).…”
Section: Resultssupporting
confidence: 73%
“…The T3 treatment increased the TAS value compared with the T1 treatment (P <0.05). Within a row, means with a common superscript were not different at probability P =0.05; βA: beta alanine T1: eggs not injected, T2: eggs injected with 0.9% sterile saline solution, T3: eggs injected with 1% βA solution, T4: chicks supplemented with βA for seven days after hatching, FCR: feed conversion ratio Within a row, means with a common superscript were not different at probability P =0.05 T1: eggs not injected, T2: eggs injected with 0.9% sterile saline solution, T3: eggs injected with 1% βA solution, T4: chicks supplemented with βA for seven days after hatching, WHC: water-holding capacity, CIE L*: lightness (black = 0 and white = 100), CIE a*: green-red opponent colours <0 indicates greenness, >0 indicates redness, CIE b*: blue-yellow opponent colours (<0 indicates blueness, >0 indicates yellowness) Kop-Bozbay et al (2018) observed that in ovo feeding of βA at a dose of 0.75% increased CW by 7.4%. In the current study, T3 produced a 4.95% increase in CW at hatching compared with the control group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation